Selective KRAS G12C inhibitors in non-small cell lung cancer: chemistry, concurrent pathway alterations, and clinical outcomes - Gabriela Palma (Nature Portfolio, 2021)
Abstract Cancers harboring mutations in the Kirsten rat sarcoma homolog (KRAS) gene have been associated with poor prognosis and lack of targeted therapies. KRAS mutations occur in approximately one in four patients diagnosed with non-small cell lung cancer (NSCLC) with KRAS G12C mutations harbored at approximately 11–16%. Research into KRAS-driven tumors and analytical chemistry have borne a new class of selective small molecules against the KRAS G12C isoform. Phase II data for sotorasib (AMG510) has demonstrated a 37.1% overall response rate (ORR). Adagrasib (MRTX849) has demonstrated a 45% ORR in an early study. While single agent efficacy has been seen, initial data suggest combination approaches are an opportunity to improve outcomes. Here, we present perspectives on the initial progress in targeting KRAS G12C, examine co-mutations evident in KRAS G12C NSCLC, and comment on potential future combinatorial approaches including SHP2, SOS1, MEK, EGFR, mTOR, CDK, and checkpoint blockade which are currently being evaluated in clinical trials. As of May 28, 2021, sotorasib has achieved US FDA approval for patients with KRAS G12C mutant lung cancer after one line of a prior therapy.